Excellent Response of Infantile Hemangioma with Oral Propranolol: A Case Report - Denissafitri, Armyta; Pramitha, Riezky Januar; Yuri Widia; Zulkarnain, Iskandar; Irmadita Citrashanty; Sawitri, Sawitri (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Infantile hemangioma (IH) is the most common benign tumor in infancy. Most IHs resolve spontaneously and do not require treatment. Therapeutic intervention is necessary for life-threatening IH, tumors posing functional risks, ulceration, and severe anatomic distortion, especially on the face. Beta-blockers, most specifically propranolol, have been shown to induce involution of IH, which should be administered as early as possible to avoid potential complications. Purpose: To report a case of IH with visual impairment treated successfully using oral propranolol. Case: A 4-month-old girl weighing, 6.3 kg, with redness plaques on the right face since 3 weeks after birth. The lesions rapidly increased in size within 2 months, and the lesions on her right eyelid made it difficult to open her right eye. Dermatological examination showed erythematous plaques, compressible and varying in size and ptosis. The patient was diagnosed with periocular infantile hemangioma and was given oral propranolol therapy with an initiated dose 3x1 mg. The dose was increased gradually. The lesions were significantly decreased and she could open her right eye normally after 5 months of propranolol therapy. Discussion: Some cases of IH require early treatment. Early treatment is indicated for IH causing functional impairment. The use of propranolol in the management of IH is very effective in the reduction of the lesions and Has minimal side effects. Conclusion: Early diagnosis and intervention with propranolol for IH play an important role in determining the optimal outcomes.